Efektifitas Minuman Bekatul Terhadap Kadar LDL dan HDL Siswa Sekolah Dasar Yang Obesitas - Abdul Azis Akbar (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2021)
Rice bran comes from rice waste which has many benefits, one of which is good for obesity because it contains lot of fiber and antioxidant gamma orizanol. This study aims to determine effect of drink rice bran much as 30 g to HDL and LDL levels of obese students several elementary schools in Makassar. The number of samples needed was 60 obese elementary school students with research design Nonequivalent Control Group Design. The results showed that the characteristics of the respondents indicated that the value was not significant between control and intervention groups. For energy intake in control group increased significantly (p = 0.061), while the intervention group experienced an increase, although not significantly (p = 0.256). Fiber intake, cholesterol, carbohydrates and fat increased in both groups but not significantly. For LDL levels in the intervention group (p = 0.000) and control group (p = 0.021) decreased significantly. while for HDL levels there was a significant increased in the intervention group (p = 0.014) and significant decreased in control group (p = 0.102). It is concluded that the provision of rice bran based drinks has an effect on reducing LDL levels and increasing HDL in obese students